Methods matter: Exploring how expectations influence common actions - Andrea Ghiani; David Mann; Eli Brenner (iScience, 2024)
Summary: Behavior in controlled laboratory studies is not always representative of what people do in daily life. This has prompted a recent shift toward conducting studies in natural settings. We wondered whether expectations raised by how the task is presented should also be considered. To find out, we studied gaze when walking down and up a staircase. Gaze was often directed at steps before stepping on them, but most participants did not look at every step. Importantly, participants fixated more steps and looked around less when asked to navigate the staircase than when navigating the same staircase but asked to walk outside. Presumably, expecting the staircase to be important made participants direct their gaze at more steps, despite the identical requirements when on the staircase. This illustrates that behavior can be influenced by expectations, such as expectations resulting from task instructions, even when studies are conducted in natural settings.